2010
DOI: 10.1192/pb.bp.109.027086
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic polypharmacy – confusion reigns

Abstract: SummaryPolypharmacy is usually employed where single drugs are considered insufficiently effective. Some polypharmacy is rational and evidence based, some neither. Antipsychotic polypharmacy remains stubbornly widespread despite condemnation of the practice by numerous bodies. The practice could not be said to be evidence based. Its persistence probably stems from a well-meaning desire to improve response and from confusion about the mechanism of action of antipsychotics. In particular, the concept that more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…In turn this allows patients a better chance of establishing some control over their illness and, with it, a measure of improved insight [Lambert et al 2009]. This study also found that high-dose (>100%BNF) antipsychotic prescribing and polyantipsychotic use is evident for patients on CTOs, although to a lesser extent than that reported for other UK samples [Tungaraza et al 2010;Paton et al 2008], despite guidelines to the contrary [Langan and Shajahan, 2010;Taylor, 2010a; National Institute for Clinical Excellence, 2009]. Compelling any patient to have potentially dangerous or even fatal high doses of medication is extremely problematic.…”
Section: Medicationmentioning
confidence: 83%
“…In turn this allows patients a better chance of establishing some control over their illness and, with it, a measure of improved insight [Lambert et al 2009]. This study also found that high-dose (>100%BNF) antipsychotic prescribing and polyantipsychotic use is evident for patients on CTOs, although to a lesser extent than that reported for other UK samples [Tungaraza et al 2010;Paton et al 2008], despite guidelines to the contrary [Langan and Shajahan, 2010;Taylor, 2010a; National Institute for Clinical Excellence, 2009]. Compelling any patient to have potentially dangerous or even fatal high doses of medication is extremely problematic.…”
Section: Medicationmentioning
confidence: 83%
“…12 The evidence base for the necessity and utility of monitoring is weak. However, psychiatrists need to bear in mind that their practices may result in high-dose prescriptions, which current guidelines state require monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…11 In an editorial which stimulated debate about additional antipsychotic prescribing in general, [12][13][14] Taylor stated that additional antipsychotic usage with clozapine is unlikely to be of value other than in the cases of cross-tapering when switching, rapid tranquillisation or specifically with the addition of aripiprazole. High-dose regimens, causing increased rates of dose-related adverse events including QT elongation, 15 can result from clozapine when used alongside other antipsychotics.…”
Section: Electrocardiogram (Ecg) Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is significant evidence that they reduce bed use, are cost-effective and patients prefer them to admission. 1 A CRHT team is dependent on the expertise and imagination of its staff to help understand and resolve a crisis. However, the risk to staff of working intensively with people who would otherwise be in hospital is not well documented.…”
Section: Risk To Staff In a Crisis Resolution Teammentioning
confidence: 99%